2014
DOI: 10.1159/000366454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Uric Acid on Hearts of Rats with Chronic Kidney Disease

Abstract: Aims: To study the effects of uric acid on cardiac lesions and its possible mechanism by establishing an early-stage CKD animal model with hyperuricemia. Allopurinol was used to see whether it could reduce cardiac lesions. Methods: The experimental rats were randomly divided into 4 groups (n = 15): Group A (sham-operative group), Group B (CKD group), Group C (CKD with hyperuricemia group), Group D (CKD with hyperuricemia + allopurinol group). After 16 weeks, the rats were sacrificed and blood samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The animal model was established as described [17]. Briefly, 20 male Sprague-Dawley rats (220~250 g, 6~8 weeks old) were obtained from Hunan Slac Jingda Experimental Animal Co. Ltd. (Changsha, China) and kept in the animal experimental center of the First Affiliated Hospital of Hunan Normal University (Changsha, China).…”
Section: Methodsmentioning
confidence: 99%
“…The animal model was established as described [17]. Briefly, 20 male Sprague-Dawley rats (220~250 g, 6~8 weeks old) were obtained from Hunan Slac Jingda Experimental Animal Co. Ltd. (Changsha, China) and kept in the animal experimental center of the First Affiliated Hospital of Hunan Normal University (Changsha, China).…”
Section: Methodsmentioning
confidence: 99%
“…Allopurinol is a competitive inhibitor of xanthine oxidase, which reduces the generation of UA. As a traditional UA‐lowering drug, allopurinol is routinely used to treat gout . However, adverse effects limit its effectiveness .…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is not enough to prevent the further deterioration of cardiac function and might further cause serious problems such as ischemia–reperfusion injury. It has been reported that high uric acid (UA) is closely related with cardiovascular disease, and the severity of cardiac lesions is positively related to the level of serum UA [ 1 , 2 ]. Meanwhile, UA can induce the endothelial dysfunction, and this effect might associate with decreased intracellular ATP, mitochondrial alterations [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%